2006
DOI: 10.1021/la053186u
|View full text |Cite
|
Sign up to set email alerts
|

Surface Pressure Driven Supramolecular Architectures from Mixed H-Aggregates of Dye-Capped Azobenzene Derivative

Abstract: We demonstrate a soft chemical approach for the synthesis of dimensionally dictated functionalized mesostructures by continuous tuning of the surface molecular density of a photoreceptable molecule (E)-1-(3-chloro-4-(octyloxy)phenyl)-2-phenyldiazene (compound 1) with Rhodamine B (Rh B). Highly oriented cylindrical microtubules with a hollow center running the entire distance of the assembly in a parallel-packed configuration were formed at the air-water interface. The surface tension driven self-organized stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…For the spin-coated film, the shift is larger than that for the vesicle, which means that the aggregation number (the number of azobenzene units within an aggregate) increased during the drying process, according to BenisiHildebrand kinetics. [20] This explanation can be further confirmed by the dialysis experiment of the self-assembled microvesicles. In Figure 3, the blue-shift induced by H-aggregation was found to gradually increase with the elongation of the dialyzing time, during which the water content gradually increased and the polarity of the solution increased at the same time.…”
Section: Uv-vis Spectroscopymentioning
confidence: 67%
See 1 more Smart Citation
“…For the spin-coated film, the shift is larger than that for the vesicle, which means that the aggregation number (the number of azobenzene units within an aggregate) increased during the drying process, according to BenisiHildebrand kinetics. [20] This explanation can be further confirmed by the dialysis experiment of the self-assembled microvesicles. In Figure 3, the blue-shift induced by H-aggregation was found to gradually increase with the elongation of the dialyzing time, during which the water content gradually increased and the polarity of the solution increased at the same time.…”
Section: Uv-vis Spectroscopymentioning
confidence: 67%
“…H-aggregation is one kind face-to-face packing of molecules with a plane shape, and such a packing state would result in an energy rise (dipole parallel, transition permitted) and an energy decrease (dipole anti-parallel, transition forbid- den), showing the maximum-absorption peak blueshifting. [8] Although the azobenzene derivatives were thought to form enthalpically pre-micellar ordered H-aggregates, [20] some works showed that within a spherical micelle containing azobenzene surfactants, H-aggregation did not occur. [21] The difference between surfactants and polymers is mainly caused by the length of the molecules' tethered azobenzene units.…”
Section: Uv-vis Spectroscopymentioning
confidence: 99%
“…[28][29][30] Among the molecular entities capable of forming ordered aggregates, azobenzenes are unique because of their intrinsic photoresponsive property. [31][32][33][34][35][36][37][38] Azobenzenes of donor-acceptor type have been found to form characteristic aggregates depending on the solvent composition, polarity, and the solute concentration.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Consequently, patterned nanoarrays, nanostripes, nanofibers, nanoparticles, nanotubes, and even chiral assemblies could be fabricated. [24,[27][28][29][30] For example, Chen et al reported that by taking the advantage of their thinner and flexible gold nanowires (AuNWs) building blocks, giant superlattice nanomembranes could be fabricated via LB techniques. [31,32] It was found that high transparency, conductivity, and stretchability could be achieved simultaneously in such single-layer AuNWs superlattice nanomembrane, which make them facile to be integrated into lightweight, foldable optoelectronic devices with low consumption of materials and energy.…”
Section: Controllable Nanoassembly Of π-Conjugated Systemsmentioning
confidence: 99%
“…Nevertheless, recent investigations found that uniaxial compression of a nanocrystal or nanowire monolayer floating on an aqueous subphase could cause such nanostructures to assemble and pack over a large area, just like “logs‐on‐a‐river” showing in Figure A . Consequently, patterned nanoarrays, nanostripes, nanofibers, nanoparticles, nanotubes, and even chiral assemblies could be fabricated . For example, Chen et al reported that by taking the advantage of their thinner and flexible gold nanowires (AuNWs) building blocks, giant superlattice nanomembranes could be fabricated via LB techniques .…”
Section: Controllable Nanoassembly Of π‐Conjugated Systemsmentioning
confidence: 99%